Political Institutions and Human Development : Does Democracy Fulfill its 'Constructive' and 'Instrumental' Role? - Vollmer, Sebastian (2012)
Institutions are a major field of interest in the study of development processes. The authors contribute to this discussion concentrating our research on political institutions and their effect on the non-income dimensions of human development. First, they elaborate a theoretical argument why and under what conditions democracies compared to autocratic political systems might perform better with regards to the provision of public goods. Due to higher redistributive concerns matched to the needs of the population democracies should show a higher level of human development. In the following they analyze whether our theoretical expectations are supported by empirical facts. The authors perform a static panel analysis over the period of 1970 to 2003. The model confirms that living in a democratic system positively affects human development measured by life expectancy and literacy rates even controlling for GDP. By analyzing interaction effects they find that the performance of democracy is rather independent of the circumstances. However, democracy leads to more redistribution in favor of health provision in more unequal societies.